Comparative Study of Raw and Boiled Silver Pomfret Fish from Coastal Area and Retail Market in Relation to Trace Metals and Proximate Composition - Roksana Huque; M. Kamruzzaman Munshi; Afifa Khatun; Mahfuza Islam; Afzal Hossain; Arzina Hossain; Shirin Akter; Jamiul Kabir; Yeasmin Nahar Jolly; Ashraful Islam (International Journal of Food Science)
Trace metals concentration and proximate composition of raw and boiled silver pomfret (Pampus argenteus) from coastal area and retail market were determined to gain the knowledge of the risk and benefits associated with indiscriminate consumption of marine fishes. The effects of cooking (boiling) on trace metal and proximate composition of silver pomfret fish were also investigated. Trace element results were determined by the Energy Dispersive X-ray Fluorescence (EDXRF) Spectrometer wherein fish samples from both areas exceeded the standard limits set by FAO/WHO for manganese, lead, cadmiumm and chromium and boiling has no significant effects on these three metal concentrations. Long-term intake of these contaminated fish samples can pose a health risk to humans who consume them.